Cognitive-affective Neuroscience of Mass Dance: Toward a New Paradigm in Dance Research - SAITO, Takahiro (Choreologia, 2008)
The experience in mass dance emerges from the interaction among dancing people through the perception and execution of movements and sounds. From the ancient ritual to the contemporary raves, a typical form of mass dance is recognized as the repetition of unison movement. Absorbed in the rhythmical sequence, one may even reach the experience of trance. This strong emotional engagement in mass dance consists of several neuropsychological stages; i) motor entrainment to the external rhythm which was generated by the bodily movement of other dancers and/or musical accompaniment, ii) emotional contagion to others, and iii) the culmination to ecstatic state through the repetition of movement. Each stage has the neural correlate of its experience. Motor entrainment via visual interaction between subjects is thought to be processed in the mirror neuron system (MNS). The neural correlates of empathy may also involve MNS as well as cortical midline structures (CMS) which are concerned with representing the self. Emotional contagion may occur under an altered state of consciousness, in which the functional derangement of cortical-subcortical neural networks of CMS is thought to be involved. Finally, the strong emotional experience can be attributed to the function of reward system, especially orbitofrontal cortex which can be related to the social intimacy and hedonic experience during dancing with others. The psychopharmacological effects of 3, 4-methylenedioxymet hamphetamine (MDMA) on both rats and humans facilitate the social communication, and may even potentiate hedonic experience by modulating the function of the orbitofrontal cortex. The mechanism of MNS and CMS thus provides neural substrate to motor entrainment to perceived external stimuli and emotional contagion. The ultimate experience in mass dance is thus hypothesized to be a product of the activation of the reward-related mechanism, motor entrainment, and emotional contagion. To elucidate in depth the neural correlates of mass dance, new research methods including neuroimaging techniques should be established.